2022
DOI: 10.3390/children9060831
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Differentiation between a Normal Anus, Anterior Anus, Congenital Anal Stenosis, and Perineal Fistula: Definitions and Consequences—The ARM-Net Consortium Consensus

Abstract: In the past, an anteriorly located anus was often misdiagnosed and treated as an anorectal malformation (ARM) with a perineal fistula (PF). The paper aims to define the criteria for a normal anus, an anterior anus (AA) as an anatomic variant, and milder types of ARM such as congenital anal stenosis (CAS) and PF. An extensive literature search was performed by a working group of the ARM-Net Consortium concerning the subject “Normal Anus, AA, and mild ARM”. A consensus on definitions, clinical characteristics, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 104 publications
0
4
0
2
Order By: Relevance
“…It is suggested that low anomaly forms with a fistula to the perineum of ARM cases are often undiagnosed (Aldeiri et al, 2019; Amerstorfer et al, 2022; Jonker, Trzpis, & PMA, 2017). Our study may have also missed this special cases of ARM that were diagnosed after the surveillance follow‐up ended, especially in programs that could not track birth defects among babies after they were discharged from the maternity hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that low anomaly forms with a fistula to the perineum of ARM cases are often undiagnosed (Aldeiri et al, 2019; Amerstorfer et al, 2022; Jonker, Trzpis, & PMA, 2017). Our study may have also missed this special cases of ARM that were diagnosed after the surveillance follow‐up ended, especially in programs that could not track birth defects among babies after they were discharged from the maternity hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes a membrane near the dentate line may accompany. 2 Diagnosis is mainly clinical. The stenosis observed during the visual examination of the anus may be confirmed by the formula: expected anal caliber (mm) = 1.34 × body weight (kg) + 6.8.…”
Section: Dear Editormentioning
confidence: 99%
“…Pediatric Surgery Clinic, Faculty of Medicine, Yeditepe University, İstanbul, Turkey 2. Pediatrics Clinic, Faculty of Medicine, Yeditepe University, İstanbul, Turkey 3.…”
mentioning
confidence: 99%
“…Перші ознаки захворювання з'являються через 10-12 год після народження: дитина погано спить, напружується; не відходить меконій. Якщо немає кваліфікованого огляду, то через одну добу з'являється здуття живота, блювота спочатку шлунковим вмістом, а потім з домішками жовчі і кишкового вмісту [9]. Дитина відмовляється від грудей.…”
Section: вступunclassified
“…Необхідні подальші багатоцентрові дослідження або дослідження на основі реєстру, щоб з'ясувати роль прийому матір'ю медичних препаратів у розвитку АВР. Martynov, et al [9] провели бібліометричний аналіз оригінальних наукових статей про АВР, який важливий для клініцистів і науковців, щоб зрозуміти глобальну дослідницьку діяльність на цю тему.…”
Section: результати дослідженняunclassified

Anorectal developmental anomalies

Антонюк,
Пикалюк,
Слободян
et al. 2023
NCBio